Socio-economic and livelihood analyses of hilsa (Tenulosa ilisha) fishers of lower stretch of Ganga River, India - Roy, Aparna; Manna, R. K.; Sharma, A. P. (Indian Journal of Fisheries, 2016)
The present study was conducted to understand the socio-economic and livelihood features of the hilsa fishers in Hooghly-Bhagirathi river system and also to find out the reasons of decline in hilsa fishery as perceived by the fishers. Results of the analysis revealed that 60% of the hilsa fishers belonged to jele/malo community and the average experience in hilsa fishing was for about 20 years. Hilsa fishery contributed 38.84% in annual family income of fishers’ households. Lower hilsa catch in Hooghly-Bhagirathi river system during the past ten years led to large scale forced migration among the fishers’ community. The younger generation of fisherfolk had lost their interest from fishery particularly of hilsa fishery due to uncertain income. Six reasons behind decline of hilsa fishery as perceived by the fishers were documented and ranked. According to the fishers, ‘use of destructive fishing gears’ (mean score 66.06) was ranked as first among the reasons behind decline in hilsa fishery followed by ‘erratic rainfall’ (64.54); ‘huge catch of hilsa fish in lower part of Hooghly/sea mouth’ (60.3); ‘industrial pollution in Hooghly River’ (52.3) and ‘freshwater discharge/influx’ (35.07). Poor implementation of mesh size regulation, poor enforcement of closed season in rivers, ineffective extension services, and recurring climatic hazards made the hilsa fishery more vulnerable. The government, fishery cooperatives, NGOs and other related organisations need to join hands to support the hilsa fishers for sustainable hilsa fishery management.